PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS JOYFUL LEARNING PADA MATERI MEMBILANG DAN OPERASI HITUNG KELAS 1 MI/SD - Sa’adah, Aulia Muthiatus; Ardhianshih, Farahustina; Rahayu, Siwi; Novita, Dwi Ayu; Malik, Muh Syauqi (FASHLUNA, 2023)
This research is motivated by the views of many students who consider learning Mathematics difficult and unpleasant. It is also motivated by the characteristics of MI/SD students who like to play, move, group activities, and like experience or demonstrate or try to do something directly. As well as changes in the curriculum to an independent curriculum and technological advances. From these things, the researcher wants to develop teaching materials that aim to produce independent curriculum teaching materials based on joyful learning to create enjoyable Mathematics learning for students which is also equipped with activities using technology. The teaching material developed is in the form of student worksheets based on joyful learning on material for numeration and arithmetic operations for class 1 MI/SD. The development method used is the Hannafin and Peck model which includes three stages, namely the needs analysis stage, design stage, development, and implementation stage. The development of LKPD is carried out by providing play and practice activities with concrete objects; songs and videos; practice questions in the form of games such as word search, crossword, and puzzles; and several website-based interactive games and quizzes from "Wordwall" which are included in the form of a QR code. Researchers also completed a package of LKPD with bags containing concrete objects.